SINONIM KATA BAIK ; al-THAYIB, al-KHAIR, al-MA’RUF, al-IHSAN, DAN as-SHOLIH DALAM AL-QUR’AN - Rusdi Fahrizal, Lalu Muhamad (el-Umdah, 2022)
Taradduf or synonyms are different word forms, but have the same meaning. This study uses the library method, researchers seek and record both from primary sources such as commentary studies, and secondary sources such as books, articles, and others. This research results that there are many similarities in meaning, but their functions and uses are different. Like the meaning of good in Indonesian, if studied in the Qur'an the word good has a different place and function.